Standardization of Semi-Quantitative Dot Blotting Assay—Application in the Diagnosis, Follow-Up, and Relapse of Paracoccidioidomycosis - Pereira, Beatriz Aparecida Soares [UNESP]; Cavalcante, Ricardo de Souza [UNESP]; Pereira-Chioccola, Vera Lucia; Melhem, Marcia de Souza Carvalho [UNESP]; de Carvalho, Lídia Raquel [UNESP]; Mendes, Rinaldo Poncio [UNESP] (MDPI, 2024)
Introduction: This study standardized a semi-quantitative dot blotting assay (DB) and a quantitative real-time polymerase chain reaction (qPCR) to detect specific antibodies for Paracoccidioides brasiliensis and its DNA in PCM patients. Methodology: We evaluated 42 confirmed PCM patients upon admission using a serological double agar gel immunodiffusion test (DID), DB, and molecular tests (qPCR in total blood). The control groups included 42 healthy individuals and 37 patients with other infectious diseases. The serological progress during treatment was evaluated in eight patients, and there was a relapse diagnosis in ten patients using the Pb B.339 strain antigen. The cut-off points for the serological tests were determined by a receiver operator characteristic curve. Results: The DB and DID tests showed similar accuracy, but the DB identified lower antibody concentrations. Cross-reactions were absent in the DB assay. In the relapse diagnoses, DB exhibited much higher sensitivity (90%) than DID (30%). Conclusions: A DB assay is easier and faster than a DID test to be performed; DB and DID tests show the same accuracy, while blood qPCR is not recommended in the diagnosis at the time of admission; cross-reactions were not observed with other systemic diseases; DB and DID tests are useful for treatment monitoring PCM patients; and a DB assay is the choice for diagnosing relapse. These findings support the introduction of semi-quantitative DB assays in clinical laboratories.
Keywords: diagnosis; dot blotting; paracoccidioidomycosis; relapse; serology